Groundwater Study in Makassar Region With Using Geoelectricity Resistant Type - Nawir, Alfian; Kamal, Zulkifli; Anshariah, Anshariah (Journal of Geology and Exploration, 2022)
One area that has the potential to experience problems with the management and utilization of groundwater is the Makassar area. Several locations in Makassar are experiencing drought, while groundwater is abundant in other parts. In some places, groundwater availability is quite good, but it isn't easy to obtain in others. Of course, this cannot be separated from the hydrogeological conditions in the Makassar area. The purpose of this research is to identify and map the distribution of groundwater in Makassar City. The research uses the resistivity method, with data including potential values, currents, span length, and rock types found in the research location. Based on the resistivity section, there are two types of groundwater: fresh and brackish. The water is brackish in GL1, with a resistivity range of 2.14 – 22.7 Ohm.m. In GL2, with a resistivity range of 0.1 – 728 Ohm.m, the water is Brackish - Fresh, and in GL3, with a resistivity range of 4.47 – 40.1 Ohm.m. The characteristics of the aquifer in the Makassar area are intermittent based on the depth level.